Analisis Faktor Intervensi Prioritas dan Faktor Intervensi Pendukung pada Ibu Hamil dalam Penanganan Stunting di Desa Sumpur Jaya Kecamatan Ketambe - Hasanalita, Hasanalita (Poltekkes Kemenkes Padang, 2023)
Stunting, the nutritional problems toddlers in Indonesia. Riskesdas 2018 results 30.8% of toddlers suffer from stunting. Efforts to reduce stunting are carried out through specific nutritional interventions to address direct causes. Target group of pregnant women, priority interventions and supporting interventions are carried out. Research is to analyze priority interventions the form of providing additional food and blood supplementation. Supporting interventions include calcium supplementation and pregnancy checks for stunting. This type of research is a cross sectional study. The research was in Simpur Jaya Village, Ketambe District. Research population was multiparous pregnant wome n who had children under five in July 2023 with sample 32 people. Data by observation, filling out questionnaires and interviews. The results of the study showed that 19 pregnant women who were given additional food had toddlers with stunting (100%) (pValue = 0.000). Pregnant women not consumption of Fe tablets experience stunting of 56% (pValue = 0.033). Most mothers who consume calcium, their toddlers do not experience stunting, 83.3%(pValue= 0.033). Pregnant women who do not regularly attend ANC visits experience a stunting incidence of 62.5%(pValue = 0.012). Concludes that providing additional food, consuming Fe tablets, consuming calcium and ANC examinations influence the incidence of stunting, is hoped that health workers to prevent stunting in the long term, interventions must be complemented by improving the determinants of malnutrition, such as poverty, education, burden. disease, and women's empowerment.